1997
DOI: 10.1002/(sici)1096-9861(19970825)385:2<230::aid-cne4>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of primary endings in deaf white cats: Morphologic alterations in endbulbs of held

Abstract: Changes in structure and function of the auditory system can be produced by experimentally manipulating the sensory environment, and especially dramatic effects result from deprivation procedures. An alternative deprivation strategy utilizes naturally occurring lesions. The congenitally deaf white cat represents an animal model of sensory deprivation because it mimics a form of human deafness called the Scheibe deformity and permits studies of how central neurons react to early-onset cochlear degeneration. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
119
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(133 citation statements)
references
References 68 publications
13
119
0
Order By: Relevance
“…It is interesting to note that in congenitally deaf white cats, degenerative alterations in individual auditory nerve synapses of the AVCN endbulbs of Held observed by Ryugo et al (1997) were largely reversed by 3 months of electrical stimulation via a cochlear implant (Ryugo et al, 2005). Specifically, in these early deafened animals (suggested to model Scheibe dysplasia), the authors reported reduced terminal branching of the endbulbs of Held, reduction in synaptic vesicle density, striking hypertrophy of the postsynaptic densities and enlargement of synapse size.…”
Section: Topography Of Auditory Nerve Projections To the Cochlear Nucmentioning
confidence: 99%
“…It is interesting to note that in congenitally deaf white cats, degenerative alterations in individual auditory nerve synapses of the AVCN endbulbs of Held observed by Ryugo et al (1997) were largely reversed by 3 months of electrical stimulation via a cochlear implant (Ryugo et al, 2005). Specifically, in these early deafened animals (suggested to model Scheibe dysplasia), the authors reported reduced terminal branching of the endbulbs of Held, reduction in synaptic vesicle density, striking hypertrophy of the postsynaptic densities and enlargement of synapse size.…”
Section: Topography Of Auditory Nerve Projections To the Cochlear Nucmentioning
confidence: 99%
“…Both congenital deafness and neonatal deafening cause structural abnormalities in the brainstem circuits that process ITD, including the endbulbs of Held in ventral cochlear nucleus (Ryugo et al 1997;Ryugo et al 1998;Lee et al 2003;Ryugo et al 2010) and inhibitory synapses onto MSO neurons (Tirko and Ryugo 2012). Chronic diotic stimulation using clinical CI processors largely reverses these changes (O'Neil et al 2010;Tirko and Ryugo 2012).…”
Section: Effect Of Deafness On Spontaneous Activitymentioning
confidence: 99%
“…Studies in the congenitally deaf white cat reveal that synapses of auditory nerve endings are abnormal, such as between end bulbs of Held and spherical bushy cells [18][19][20], as well as between modified end bulbs and globular bushy cells [21]. In addition, the synaptic abnormalities are present at an early age (6 months) in the deaf white cat.…”
Section: Effects Of Symmetrical Profound Hearing Loss On the Auditorymentioning
confidence: 99%